26.0k views
14 votes
Write the first 6 terms of the sequence.

an= -n2+6

Please show work

User Gldanoob
by
5.0k points

2 Answers

9 votes

Answer:

Explanation:


a_(n)=-n^2+6\\a_(1)=-1^2+6=5\\a_(2)=-2^2+6=2\\a_(3)=-3^2+6=-3\\a_(4)=-4^2+6=-10\\a_(5)=-5^2+6=-25+6=-19\\a_(6)=-6^2+6=-36+6=-30

User Aatch
by
5.9k points
6 votes
For the term number which is “n” you substitute for example to find the first term you would do

(-1)(2)+6= 4

For term two replace “n” with 2

(-2)(2)+6= 2

Then you would continue for the rest of the terms
User Milovanderlinden
by
4.6k points